1998
DOI: 10.1007/bf02446923
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and clinical validation of plasmadynamic therapy of wounds with nitric oxide

Abstract: Pronounced wound-healing effect of exogenous nitric oxide obtained by the plasma chemical method was confirmed in rats with aseptic and infected wounds and in patients with complicated stubborn wounds, postradiation and trophic ulcers, necroses of transplanted skin flaps, etc. Morphological study revealed normalization of microcirculation, decreased inflammation, enhanced phagocytosis, activation of macrophages, and accelerated proliferation of fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 3 publications
0
55
1
1
Order By: Relevance
“…A major task will be the introduction of plasma into clinical medicine and, simultaneously, the further investigation of the mechanisms of action of plasma at the cellular level. [35,36]. Unter anderem werden dafür eine Vasodilatation und normalisierte Mikrozirkulation, direkte bakterizide Effekte, Verbesserung der Nervenleitgeschwindigkeit, Stimulierung von Fibroblasten und Gefäßwachstum durch Induktion von Zytokinen und Wachstumsfaktoren verantwortlich gemacht.…”
Section: Discussionunclassified
“…A major task will be the introduction of plasma into clinical medicine and, simultaneously, the further investigation of the mechanisms of action of plasma at the cellular level. [35,36]. Unter anderem werden dafür eine Vasodilatation und normalisierte Mikrozirkulation, direkte bakterizide Effekte, Verbesserung der Nervenleitgeschwindigkeit, Stimulierung von Fibroblasten und Gefäßwachstum durch Induktion von Zytokinen und Wachstumsfaktoren verantwortlich gemacht.…”
Section: Discussionunclassified
“…On the one hand, it was recognized that the levels of nitric oxide in deep wounds and scars are reduced in comparison to its amount in healthy tissue [35][36]. In our previous investigations the high efficacy of plasma gNO therapy was observed in the treatment of radiation-induced skin fibrosis in cancer patients [6,37]. It also has been shown that plasma gNO therapy of wounds results in almost all cases in the formation of rather gentle cosmetic scars even in purulent and chronic recalcitrant lesions [38,39,40].…”
Section: Plasma Gno Therapy Of Skin Scarsmentioning
confidence: 97%
“…In previous publications [6,7] we briefly reported that the use of plasma-generated gNO provides significant therapeutic effects in treatment of several pathologies (Fig. 1).…”
mentioning
confidence: 97%
See 2 more Smart Citations